Benthic invaders control the phosphorus cycle in the world’s largest freshwater ecosystem - Li, Jiying (Proc Natl Acad Sci U S A, 2021)
The productivity of aquatic ecosystems depends on the supply of limiting nutrients. The invasion of the Laurentian Great Lakes, the world’s largest freshwater ecosystem, by dreissenid (zebra and quagga) mussels has dramatically altered the ecology of these lakes. A key open question is how dreissenids affect the cycling of phosphorus (P), the nutrient that limits productivity in the Great Lakes. We show that a single species, the quagga mussel, is now the primary regulator of P cycling in the lower four Great Lakes. By virtue of their enormous biomass, quagga mussels sequester large quantities of P in their tissues and dramatically intensify benthic P exchanges. Mass balance analysis reveals a previously unrecognized sensitivity of the Great Lakes ecosystem, where P availability is now regulated by the dynamics of mussel populations while the role of the external inputs of phosphorus is suppressed. Our results show that a single invasive species can have dramatic consequences for geochemical cycles even in the world’s largest aquatic ecosystems. The ongoing spread of dreissenids across a multitude of lakes in North America and Europe is likely to affect carbon and nutrient cycling in these systems for many decades, with important implications for water quality management.